The Influence of Music Culture on The Peoples of Central Asia in The Development of Uzbek Music Culture (Eurasian Journal of Humanities and Social Sciences, 2022)
The article provides an overview of the culture of the peoples of Central Asia up to the XVIII century. In addition, the role of factors in the development of Uzbek music culture was discussed.